2021
DOI: 10.1016/j.healthpol.2021.05.003
|View full text |Cite
|
Sign up to set email alerts
|

How to make universal, voluntary testing for COVID-19 work? A behavioural economics perspective

Abstract: Testing is widely seen as one core element of a successful strategy to curtail the COVID-19 pandemic and many countries have increased their efforts to provide testing at large scale. As most democratic governments refrain from enacting mandatory testing, a key emerging challenge is to increase voluntary participation. Using behavioural economics insights complemented with data from a novel survey in the US and a survey experiment in Luxembourg, we examine behavioural factors associated with the individual wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 33 publications
2
10
0
Order By: Relevance
“…Regarding the uptake of COVID-19 testing, although some areas had not reported any confirmed cases, over half of respondents reported having received or scheduled a test. Except for occupation, no socio-demographic characteristic was associated with the willingness and uptake of COVID-19 testing, which is consistent with previous studies [ 53 , 62 ]. This indicated the equal willingness and access to COVID-19 testing in China, which may lie in the fact that the Chinese central government and some local governments require healthcare providers to supply the community-wide mass COVID-19 testing without cost-sharing and the testing policies for travel [ 63 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Regarding the uptake of COVID-19 testing, although some areas had not reported any confirmed cases, over half of respondents reported having received or scheduled a test. Except for occupation, no socio-demographic characteristic was associated with the willingness and uptake of COVID-19 testing, which is consistent with previous studies [ 53 , 62 ]. This indicated the equal willingness and access to COVID-19 testing in China, which may lie in the fact that the Chinese central government and some local governments require healthcare providers to supply the community-wide mass COVID-19 testing without cost-sharing and the testing policies for travel [ 63 ].…”
Section: Discussionsupporting
confidence: 91%
“…In addition, higher awareness of and perceived susceptibility to COVID-19 were positively associated with the respondent’s willingness to receive and uptake of COVID-19 testing and vaccination, which concurs with data from previous studies reporting that perceiving a high risk of infections may increase willingness and uptake rates for both testing and vaccination [ 29 , 33 , 42 – 47 , 53 , 62 , 75 , 76 ].…”
Section: Discussionsupporting
confidence: 89%
“…In a recent study from the US, Thunström et al (2021) found that healthy younger people were more likely to take a no-cost COVID-19 test than health older people, with people generally selfless in their decision to test for COVID-19 [ 14 ]. In contrast, Fallucchi et al (2021) found that willingness-to-test was increased in association with altruism, conformism and risk-aversion and decreased with decreasing age and increased willingness to take risks [ 15 ]. Messaging tailored to our students with an emphasis on personal benefits or rewards may have been more successful.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, when an individual's fear of infection increases, the psychological costs also increase. The individual's perceived expected benefits from protecting others are also relatively large, and the individual's willingness to engage in preventative health behaviors also increases [26].…”
Section: Factors Influencing Altruistic Behaviorsmentioning
confidence: 99%
“…From a utilitarian perspective, benefit is a measure that takes into account the individual's material and psychological benefits and costs [17,18]. An individual's fear of disease infection may have a psychological cost, which in turn prompts the individual to engage in corresponding preventive health behaviors [25,26]. However, the measures required by these preventative health behaviors may also increase the psychological and material costs individuals face, such as inconvenience resulting from changes in daily living habits [18] or the loss of personal resources from donating materials or providing unpaid services, which reduces individuals' probability of engaging in preventative health behaviors.…”
Section: Anxiety Perception and Preventative Health Behaviorsmentioning
confidence: 99%